Therapeutic endoscopic ultrasound: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - van der Merwe, Schalk W.; van Wanrooij, Roy L. J.; Bronswijk, Michiel; Everett, Simon; Lakhtakia, Sundeep; Rimbas, Mihai; Hucl, Tomas; Kunda, Rastislav; Badaoui, Abdenor; Law, Ryan; Arcidiacono, Paolo G.; Larghi, Alberto; Giovannini, Marc; Khashab, Mouen A.; Binmoeller, Kenneth F.; Barthet, Marc; Perez-Miranda, Manuel; van Hooft, Jeanin E. (Endoscopy, 2021)
1 ESGE recommends the use of endoscopic ultrasound-guided biliary drainage (EUS-BD) over percutaneous transhepatic biliary drainage (PTBD) after failed endoscopic retrograde cholangiopancreatography (ERCP) in malignant distal biliary obstruction when local expertise is available.Strong recommendation, moderate quality evidence.2 ESGE suggests EUS-BD with hepaticogastrostomy only for malignant inoperable hilar biliary obstruction with a dilated left hepatic duct when inadequately drained by ERCP and/or PTBD in high volume expert centers.Weak recommendation, moderate quality evidence.3 ESGE recommends that EUS-guided pancreatic duct (PD) drainage should only be considered in symptomatic patients with an obstructed PD when retrograde endoscopic intervention fails or is not possible.Strong recommendation, low quality evidence.4 ESGE recommends rendezvous EUS techniques over transmural PD drainage in patients with favorable anatomy owing to its lower rate of adverse events.Strong recommendation, low quality evidence.5 ESGE recommends that, in patients at high surgical risk, EUS-guided gallbladder drainage (GBD) should be favored over percutaneous gallbladder drainage where both techniques are available, owing to the lower rates of adverse events and need for re-interventions in EUS-GBD.Strong recommendation, high quality of evidence.6 ESGE recommends EUS-guided gastroenterostomy (EUS-GE), in an expert setting, for malignant gastric outlet obstruction, as an alternative to enteral stenting or surgery.Strong recommendation, low quality evidence.7 ESGE recommends that EUS-GE may be considered in the management of afferent loop syndrome, especially in the setting of malignancy or in poor surgical candidates. Strong recommendation, low quality evidence.8 ESGE suggests that endoscopic ultrasound-directed transgastric ERCP (EDGE) can be offered, in expert centers, to patients with a Roux-en-Y gastric bypass following multidisciplinary decision-making, with the aim of overcoming the invasiveness of laparoscopy-assisted ERCP and the limitations of enteroscopy-assisted ERCP.Weak recommendation, low quality evidence.